Optimisation of low and ultra-low dose scanning protocols for ultra-extended field of view PET in a real-world clinical setting - Johanna Ingbritsen; Jason Callahan; Hugh Morgan; Melissa Munro; Robert E. Ware; Rodney J. Hicks (Cancer Imaging)
Abstract True total-body and extended axial field-of-view (AFOV) PET/CT with 1m or more of body coverage are now commercially available and dramatically increase system sensitivity over conventional AFOV PET/CT. The Siemens Biograph Vision Quadra (Quadra), with an AFOV of 106cm, potentially allows use of significantly lower administered radiopharmaceuticals as well as reduced scan times. The aim of this study was to optimise acquisition protocols for routine clinical imaging with FDG on the Quadra the prioritisation of reduced activity given physical infrastructure constraints in our facility. Low-dose (1 MBq/kg) and ultra-low dose (0.5 MBq/g) cohorts, each of 20 patients were scanned in a single bed position for 10 and 15 min respectively with list-mode data acquisition. These data were then reconstructed simulating progressively shorter acquisition times down to 30 s and 1 min, respectively and then reviewed by 2 experienced PET readers who selected the shortest optimal and minimal acquisition durations based on personal preferences. Quantitative analysis was also performed of image noise to assess how this correlated with qualitative preferences. At the consensus minimum acquisition durations at both dosing levels, the coefficient of variance in the liver as a measure of image noise was 10% or less and there was minimal reduction in this measure between the optimal and longest acquisition durations. These data support the reduction in both administered activity and scan acquisition times for routine clinical FDG PET/CT on the Quadra providing efficient workflows and low radiation doses to staff and patients, while achieving high quality images.